2013
DOI: 10.3892/ijmm.2013.1270
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analyses of peripheral whole blood cells from ulcerative colitis patients: Effects of leukocytapheresis

Abstract: Abstract.Complementary DNA microarray technology allows the simultaneous analysis of the expression of hundreds to thousands of genes. We applied this technique to clarify the molecular mechanisms underlying the therapeutic effects of leukocytapheresis (LCAP) therapy in patients with ulcerative colitis (UC). A 776-gene microarray analysis was performed using whole blood cells from six normal subjects and six patients with active UC who had undergone filtration LCAP. Widespread gene upregulation was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Since the sample size of our study is larger, the results are more comprehensive. Some unreported genes still have considerable research value due to their homology with many genes that have been confirmed to be closely related to UC in gene function (Kobayashi et al, 2013; Noble et al, 2008; Planell et al, 2013; Wu et al, 2007). Compared to other data re-analyses researches on UC, almost all of the studies were conducted directly by functional clustering for a large number of DEGs to display the main mechanisms of the disease, which can not reflect the importance of the individual genes (Feng et al, 2017; Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the sample size of our study is larger, the results are more comprehensive. Some unreported genes still have considerable research value due to their homology with many genes that have been confirmed to be closely related to UC in gene function (Kobayashi et al, 2013; Noble et al, 2008; Planell et al, 2013; Wu et al, 2007). Compared to other data re-analyses researches on UC, almost all of the studies were conducted directly by functional clustering for a large number of DEGs to display the main mechanisms of the disease, which can not reflect the importance of the individual genes (Feng et al, 2017; Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 12 , 15 Previous studies related methylation in the aryl-hydrocarbon receptor repressor ( AHRR ) gene and the Cytochrome P450, family 1, subfamily A1 ( CYP1A1 ) gene to tobacco smoke exposure in both smokers and newborns and most studies, including ours, reported the same CpG as the top signal (cg05575921). 10 , 12 , 15 , 42 , 43 Both AHRR and CYP1A1 are involved in the aryl-hydrocarbon receptor (AhR) pathway, regulating the biological responses to hydrocarbons found in cigarette smoke and xenobiotic metabolism in general. 43 45 The myosin-1 G ( MYO1G ) gene is involved in haematopoietic processes and regulation of cell elasticity.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 12 , 15 , 42 , 43 Both AHRR and CYP1A1 are involved in the aryl-hydrocarbon receptor (AhR) pathway, regulating the biological responses to hydrocarbons found in cigarette smoke and xenobiotic metabolism in general. 43 45 The myosin-1 G ( MYO1G ) gene is involved in haematopoietic processes and regulation of cell elasticity. 46 The contactin-associated protein-like 2 ( CNTNAP2 ) gene is involved in the development of the nervous system 47 and in neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ADGRE5 interacts with CD55 [6063], the glycosaminoglycan chondroitin sulfate [64, 65], integrin [66] or CD90 [67] in an isoform-specific manner. Initial functional studies suggest that ADGRE5 is relevant for cell adhesion, migration and invasion [53, 59, 68].…”
Section: Discussionmentioning
confidence: 99%